Active vibration control of CNT reinforced functionally graded plates based on a higher-order shear deformation theory. (January 2016) - Song, Z.G.; Zhang, L.W.; Liew, K.M.
Abstract: This paper presents the active vibration control of carbon nanotube (CNT) reinforced functionally graded plates using piezoelectric actuator and sensor pairs bonded on the top and bottom surfaces of the host plate. Three types of CNT distributions are considered. In this study, Reddy׳s higher-order shear deformation theory (HSDT) is applied to evaluate the displacement fields of the host plate. The equation of motion of the whole structural system is formulated by Hamilton׳s principle. To derive a set of discrete ordinary differential equation, the assumed mode method is used. For the active vibration control, velocity feedback control method is used to design the controller. Responses of the plate subjects to free and forced vibration are determined. The differences of vibrations between the three types of CNT reinforced functionally graded plates are compared. Influence of volume fraction of the CNTs on the vibration amplitude is investigated. The active vibration control effects of the velocity feedback controller are presented and the trend of change in the control effect with placements of piezoelectric patches is also examined. Highlights: Vibration characteristics of high-order CNT reinforced functionally graded plates are studied. Active vibration control for the CNT reinforced functionally graded plates are carried out. CNT distributions on the vibration behaviors of the CNT reinforced functionally graded plates are investigated. Influences of piezoelectric patches placements on the vibration control effects are analyzed.